Perceptions of Female Aggression on Reality Television - Donovan, Kathleen (Université d'Ottawa / University of Ottawa, 2016)
Despite the detrimental effects of aggression, Reality Television is replete with portrayals of female direct and indirect aggression for the sake of entertainment. Direct, physical and verbal aggression may be easy to identify but indirect aggression can be circuitous and subtle such as gossiping and exclusion from the group. Victims of indirect aggression can experience long-term psychological repercussions such as depression, anxiety, low self-esteem and self-abusive behaviour. Exposure to indirect relational aggression on Reality Television has also been shown to increase physical aggression in its viewers. Combining three theoretical frameworks this study draws on social cognitive theory, cultivation theory as well as feminist frameworks. Female adults were recruited to participate in semi-structured interviews discussing their perceptions and influence of Reality Television clips portraying female aggression.